The satisfied patient 2.0: Analysis of anonymous doctor reviews to generate a patient mood - Geierhos, Michaela; Schulze, Sabine (ForschungsForum Paderborn)

The Satisfied Patient 2.0: Analysis of anonymous doctor ratings to gain insight into patient sentimen - Geierhos, Michaela; Schulze, Sabine (ForschungsForum Paderborn)

A Technical Concept for Plant Engineering by Simulation-Based and Logistic-Integrated Project Management - Gutfeld, Thomas; Jessen, Ulrich; Wenzel, Sigrid; Laroque, Christoph; Weber, Jens (Proceedings of the 2014 Winter Simulation Conference)

A Data Mining Approach to Support a Data-Driven Scheduling System for Air Cargo Terminals - Boxnick, Simon; Lauck, Sebastian; Weber, Jens (Proceedings of the IEEE Asia-Pacific World Congress on Computer Science and Engineering 2014 (APWC on CSE 2014))

Experiments using Meta-Heuristics to Shape Experimental Design for a Simulation-Based Optimization System: Intelligent Configuration and Setup of Virtual Tooling - Weber, Jens; Boxnick, Simon; Dangelmaier, Wilhelm (Proceedings of the IEEE Asia-Pacific World Congress on Computer Science and Engineering 2014 (APWC on CSE 2014))

Applying GPU Programming to Obtain Average AS/RS Performance in Optimal Zoned Aisles - Lauck, Sebastian; Boxnick, Simon; Kopecki, Lukas (Proceedings of the IEEE Asia-Pacific World Congress on Computer Science and Engineering 2014 (APWC on CSE 2014))

Analyzing Supply Chain nodes in Heterogeneous Environments based on Transaction Data with Respect to Independent item Behavior - Lauck, Sebastian; Boxnick, Simon; Kopecki, Lukas (Proceedings of the 2nd International Conference on Advances in Computing, Electronics and Communication (ACEC-2014))

System Thinking: Crafting Scenarios for Prescriptive Analytics - Weber, Jens; Minhee, Cho; Lee, Mikyoung; Song, Sa-kwang; Geierhos, Michaela; Jung, Hanmin (Proceedings of the First International Workshop on Patent Mining and Its Applications (IPAMIN) 2014)

SentiBA: Lexicon-based Sentiment Analysis on German Product Reviews - Dollmann, Markus; Geierhos, Michaela (Konvens 2014 Workshop Proceedings)

Linked Open Data System for Scientific Data Sets - Baeumer, Frederik Simon; Gim, Jangwon; Jeong, Do-Heon; Geierhos, Michaela; Jung, Hanmin (Proceedings of the First International Workshop on Patent Mining and Its Applications (IPAMIN) 2014)

The same but not the same - Challenges in comparing patient opinions - Geierhos, Michaela; Schulze, Sabine

What is research ethics observing? An interdisciplinary {\ "a} re discussion between computational linguistics and qualitative-constructivist social research} - Geierhos, Michaela; Siri, Jasmin (Proceedings Research Ethics in Qualitative and Quantitative Social Research)

Ans {\ "a} sets for ü r an online optimization of the lot sizes in the Series production - Dangelmaier, Wilhelm

Modeling of the PLC Behavior in Intralogistics with Non-Autonomous Hybrid Petri-Nets - Kopecki, Lukas; Lauck, Sebastian

Information Systems for Composite Materials: Requirements and Challenges - Dangelmaier, Wilhelm; Sommer-Dittrich, Thomas; Streichhan, Jenny; Monhof, Markus (Applied Mechanics and Materials)

Comparative study on disambiguating acronyms in the scientific papers using the open knowledge base - Jeong, Do-Heon; Gim, Jangwon; Jung, Hanmin; Geierhos, Michaela; Baeumer, Frederik Simon (Proceedings of the 9th Asia Pacific International Conference on Information Science and Technology)

An Evolutionary Approach on Multi-objective Scheduling for Evolving Manufacturing Systems - Klöpper, Benjamin; Pater, Jan-Patrick; Dangelmaier, Wilhelm (Proceedings of the 47th Annual Hawaii International Conference on System Sciences)
New paradigms for designing manufacturing systems, such as adaptive and service-oriented manufacturing systems or self-optimizing resources, introduce new degrees of freedom into manufacturing control. These paradigms lead to the research question how human decision makers can be enabled to exploit the high adaptability of the new manufacturing systems in accordance to the current requirements arising from quickly changing market requirements and demand for sustainable manufacturing. This contribution extends a scheduling model for self-optimizing and service-oriented manufacturing systems through the consideration of alternative resources and introduces a multi-objective scheduling concept based on evolutionary algorithms in combination with a new optimized type of crossover operator.

Acceleration of Materialflow Simulations Using Model Coarsening by Token Sampling and Online Error Estimation and Accumulation Controlling - Renken, Hendrik

Towards a Local Grammar-based Persondata Generator for Wikipedia Biographies - Geierhos, Michaela (Penser le Lexique-Grammaire)

Development of the RailCab Vehicle - Flaßkamp, Kathrin; Grösbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Krüger, Martin; Ober-Blöbaum, Sina; Priesterjahn, Claudia; Rasche, Christoph; Schäfer, Wilhelm; Steenken, Dominik; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Simulation Aided, Self-Adapting Knowledge Based Control of Material Handling Systems - Klaas, Alexander; Laroque, Christoph; Renken, Hendrik; Dangelmaier, Wilhelm (Proceedings of the 2013 Winter Simulation Conference)

Collective generation of subjective situations / measures for online control in transport and storage systems} - Dangelmaier, Wilhelm; Klaas, Alexander

Simulation in Production and Logistics 2013 - Dangelmaier, Wilhelm; Laroque, Christoph; Klaas, Alexander (Proceedings 15th ASIM Conference Simulation in Production and Logistics)

Improving Flow-Based Modeling of Enterprise Systems and Modeling of Custom Warehouse Systems in d³fact - Renken, Hendrik; Dangelmaier, Wilhelm (Proceedings of the 3rd International Conference on Simulation and Modeling Methodologies, Technologies and Applications)

Evaluation of affinely adjustable robust counterpart for the CLSP - Dangelmaier, Wilhelm; Kaganova, Ekaterina

Proactive Self-Adaptation of a Flexible Simulation Based Control System Using Forecasting - Klaas, Alexander; Streit, Daniel; Schilling, Markus; Dangelmaier, Wilhelm (Proceedings of the 11th IFAC Workshop on Intelligent Manufacturing Systems)

Kaskadierte Simulationen und Visualisierungen für die Analyse mechatronischer Systeme in umfangreichen Transportszenarien - Hassan, Bassem; Klaas, Alexander; Wassmann, Helene; Grafe, Michael

A contribution to the anticipation and regulation of behavior in cognitive mechatronic systems in long-term planning and execution - Hartmann, Philip

Determination of safety requirements {\ "a} nden regarding future delivery reliability in compliance with capital commitment restrictions by means of simulation-based optimization - Pater, Jan-Patrick; Laroque, Christoph; Dangelmaier, Wilhelm; Becker, Roland
n the past, the automotive industry developed logistical concepts that were later adapted and modified by other industries. This article is based on a real scenario from the rail vehicle industry in which the introduction of JIT, kitting and complete deliveries has a negative impact on delivery reliability. In order to counteract this, a process was developed which, taking into account the target conflict of delivery reliability and capital commitment, protects the orders in the supply chain against disruptions by means of safety stocks and thus increases delivery reliability.

Current challenges in process simulation - sketch of a solution approach based on model-driven software development - Dangelmaier, Wilhelm; Laroque, Christoph (Production in Germany - Competitiveness in the 21st Century)

An Automatic Approach for Parameter Optimization of Material Flow Simulation Models based on Particle Swarm Optimization - Laroque, Christoph; Pater, Jan-Patrick
The analysis of production systems by the use of discrete, event-based simulation is widely used and accepted as decision support method. It aims either at the comparison of competitive designs or the identification of a “best possible” configuration of the simulation model. Here, combinatorial techniques of simulation and optimization methods support the user in finding optimal solutions, which typically result in long computation times and though often prohibit a practical application in today’s industry. This paper presents a fast converging procedure as a combination of a swarm heuristic, namely the particle swarm optimization, and the material flow simulation to close this gap. Faster convergence is realized by a specific extension of classic PSO implementations. First results show the applicability with a simulation reference model.

Multi-Layer Architecture for Transition of Business-Models to common Software-Tools and Optimization of the Model-Structure exemplified with Microsoft SharePoint 2010 - Lauck, Sebastian; Hartmann, Philip; Laroque, Christoph

Fast Converging, Automated Experiment Runs for Material Flow Simulations Using Distributed Computing and Combined Metaheuristics - Laroque, Christoph; Klaas, Alexander; Fischer, Jan-Hendrik; Kuntze, Mathis (Proceedings of the 2012 Winter Simulation Conference)

Application relevance of dissertations - Dangelmaier, Wilhelm

Bi-objective-optimisation of an international transportation problem for CO2-efficient schedules - Kl{\, Benjamin; Pater, Jan-Patrick; Irohara, Takashi; Xue, Yudong (International Journal of Engineering Management and Economic)
The transportation sector accounts for a considerable portion of global CO2 emissions and the demand for transport, especially for international transport, is increasing. Current approaches to reduce CO2 emission on an operational level ignore time-related objectives and focus on simultaneous optimisation of economic and ecological objectives. In general, considering the minimisation of CO2 emissions in transportation scheduling introduces a trade-off between economic and ecological concerns. The concept of eco-efficiency is important in order to evaluate the economical value and ecological quality of business decisions. Nevertheless, this concept has primarily been applied to strategic decisions. In the present paper we demonstrate the applicability of this concept to operative decisions and introduce a bi-objective evolutionary optimisation approach for the approximation of CO2-efficient schedules in an international transportation problem.

Visualization and Collaborative Editing of Simulation Models With Heterogeneous Clients - Implemented Into the Simulator d3fact - Renken, Hendrik; Eichert, Felix Alexander; Brandt, Sascha; Klaas, Alexander

Development of cost-effective spare parts logistics for a solar technology provider under monet {\ "a} rer Ber ü consideration of resulting CO2 emissions - Dangelmaier, Wilhelm; Laroque, Christoph; Delius, Robin; Streichhan, Jenny

Kontinuierliche Adaption von Lieferketten durch Leistungsbewertung und -steuerung dynamischer Geschäftsprozesse - Hartmann, Philip; Laroque, Christoph

Comparing a hybrid simulation & optimization approach with a purely stochastic optimization to increase the robustness of production plans - Fischer, Jan-Hendrik; Delius, Robin; Horstkemper, Dennis; Laroque, Christoph

Increase of robustness in production plans using a hybrid optimization and simulation approach - Laroque, Christoph; Delius, Robin; Fischer, Jan-Hendrik (International Journal on Advances in Systems and measurements)

Parallel scheduling for evolving manufacturing systems - Klöpper, Benjamin; Pater, Jan-Patrick; Dangelmaier, Wilhelm (Proceedings of the 9th IEEE International Conference on Industrial Informatics)

Building blocks of business informatics - basics and applications - Fischer, J; Dangelmaier, Wilhelm; Nastansky, Ludwig; Suhl, L

Robust solution approach to an uncertain CLSP problem - Kaganova, Ekaterina (Applied Mathematical Optimization and Modelling)

A multi-objective evolutionary approach to scheduling for evolving manufacturing systems - Kl{\, Benjamin; Pater, Jan-Patrick; Honiden, Shinichi; Dangelmaier, Wilhelm (Evolving Systems)
Persistent trends like quickly changing production programs, increasing customer individual manufacturing and Sustainable Manufacturing create complex systems of objectives in manufacturing control. Service-oriented manufacturing systems and self-optimizing manufacturing resources offer the required flexibility to consider these objectives in accordance with the current organizational and economical situation. On the downside, this increase in flexibility make the control of manufacturing systems more difficult and presents new challenges regarding the scheduling. To meet these challenges, we developed scheduling framework that supports alternative process plans and considers the internal states trajectories of resources. In order to support the user in a complex decision-making environment, evolutionary multi-objective optimization is used to generate a set of relevant schedules and an interface to select the most appropriate schedule is provided.

Cascaded Heterogeneous Simulations for Analysis of Mechatronic Systems in Large Scale Transportation Scenarios - Hassan, Bassem; Wassmann, Helene; Klaas, Alexander; Kessler, Jan Henning (Proceedings of the 2012 Emerging M&S Applications in Industry & Academia Symposium, Spring Simulation Multiconference,)

Ensuring calls to automotive suppliers with minimal costs with special consideration of liquidity {\ "a} ts-, Besch {\ "a} qualification, know-how and IT restrictions - Delius, Robin

A Cross-Level Approach To Planning Changeability in Distribution Systems - Klingebiel, Katja; Winkler, Matthes; Klaas, Alexander; Laroque, Christoph (Proceedings of the 2012 Emerging M&S Applications in Industry & Academia Symposium, Spring Simulation Multiconference)

Effektives Customer Relationship Management: Instrumente - Einführungskonzepte - Organisation - Helmke, Stefan, Stefan; Uebel, Matthias; Dangelmaier, Wilhelm

Buy, Sell, or Hold? Information Extraction from Stock Analyst Reports - Lee, Yeong Su; Geierhos, Michaela

Complexity-induced production and inventory cost in consumer goods supply chain - Danne, Christoph; Dangelmaier, Wilhelm; H{\, Petra